INFLUÊNCIA DO SEXO NA ASSOCIAÇÃO DA SÍNDROME METABÓLICA COM A DOENÇA ARTERIAL CORONARIANA - Almeida, Aiza Leal de (2011)
Studies have been conducted to determine the association between metabolic syndrome and coronary artery disease. The current perspective is to investigate whether there are gender differences in his presentation to determine significant changes in prevention and treatment. In this context, this study aimed to evaluate the association of metabolic syndrome with coronary artery disease and verify the gender difference in their characteristics. We evaluated 325 patients who consecutively underwent coronary angiography for investigation of coronary artery disease. Metabolic syndrome was defined according to criteria of National Cholesterol Education Program's Adult Treatment Panel III. It was considered as coronary artery disease the presence of obstruction in the coronary arteries demonstrated by angiography. To verify the association and distribution of their frequencies between the studied variables used the chi-square tests, Student's t, and nonparametric Mann-Whitney test. The levels of significance for all tests was α ≤ 0.05 and confidence interval of 95%. The prevalence of MS was 54.7% in men and 45.3% in women, with statistical significance. While coronary artery disease had a prevalence of 66.4% and 33.6% respectively for male and female, also statistically significant. The association SM and Coronary Artery Disease was elevated in both sexes, and more present in women, with statistical significance. Hypertriglyceridemia was the component of metabolic syndrome more common in both sexes in the presence of coronary artery disease, followed by low HDL cholesterol in men and high blood pressure in women, these differences were statistically significant. It is concluded that metabolic syndrome was highly prevalent in the population with CAD were no differences between the sexes, women were more affected by the association of metabolic syndrome and coronary artery disease.